CLINICAL EFFICIENCY OF LATERAL TEETH RECOVERY BY DOMESTIC COMPOSITE MATERIAL USING DIFFERENT FILLING TECHNIQUE - Sokolova, I.I.; German, S.I.; Biryukova, M.M. (World of Medicine and Biology, 2016)
It is well known that direct method of dental restoration with using composite materials have both advantages and bad aftereffects. The most important facts of it’s long-termed and favorable results are the destruction of marginal adaptation in enamel and dentin, especially in molars and premolars, and postoperative sensitivity connected with polymerization stress. One of the way in overcoming of this complications is the contemporary using of filling materials with different elasticity modulus. Low-modulus composites (fluid polymers) are capable to compensate the polymerization stress because of it’s high elasticity.